The Brighton Collaboration standardized template for collection of key information for risk/benefit assessment of a Modified Vaccinia Ankara (MVA) vaccine platform. Issue 22 (21st May 2021) - Volkmann, Ariane; Williamson, Anna-Lise; Weidenthaler, Heinz; Meyer, Thomas P.H.; Robertson, James S.; Excler, Jean-Louis; Condit, Richard C.; Evans, Eric; Smith, Emily R.; Kim, Denny; Chen, Robert T.; ,
Abstract: The Brighton Collaboration Viral Vector Vaccines Safety Working Group (V3SWG) was formed to evaluate the safety and characteristics of live, recombinant viral vector vaccines. The Modified Vaccinia Ankara (MVA) vector system is being explored as a platform for development of multiple vaccines. This paper reviews the molecular and biological features specifically of the MVA-BN vector system, followed by a template with details on the safety and characteristics of an MVA-BN based vaccine against Zaire ebolavirus and other filovirus strains. The MVA-BN-Filo vaccine is based on a live, highly attenuated poxviral vector incapable of replicating in human cells and encodes glycoproteins of Ebola virus Zaire, Sudan virus and Marburg virus and the nucleoprotein of the Thai Forest virus. This vaccine has been approved in the European Union in July 2020 as part of a heterologous Ebola vaccination regimen. The MVA-BN vector is attenuated following over 500 serial passages in eggs, showing restricted host tropism and incompetence to replicate in human cells. MVA has six major deletions and other mutations of genes outside these deletions, which all contribute to the replication deficiency in human and other mammalian cells. Attenuation of MVA-BN was demonstrated by safe administration in immunocompromised mice and non-human primates. In multiple clinical trials with the MVA-BN backbone, more than 7800 participants have been vaccinated, demonstrating a safety profile consistent with other licensed, modern vaccines. MVA-BN has been approved as smallpox vaccine in Europe and Canada in 2013, and as smallpox and monkeypox vaccine in the US in 2019. No signal for inflammatory cardiac disorders was identified throughout the MVA-BN development program. This is in sharp contrast to the older, replicating vaccinia smallpox vaccines, which have a known risk for myocarditis and/or pericarditis in up to 1 in 200 vaccinees. MVA-BN-Filo as part of a heterologous Ebola vaccination regimen (Ad26.ZEBOV/MVA-BN-Filo) has undergone clinical testing including Phase III in West Africa and is currently in use in large scale vaccination studies in Central African countries. This paper provides a comprehensive picture of the MVA-BN vector, which has reached regulatory approvals, both as MVA-BN backbone for smallpox/monkeypox, as well as for the MVA-BN-Filo construct as part of an Ebola vaccination regimen, and therefore aims to provide solutions to prevent disease from high-consequence human pathogens.